Anodes for lithium-ion batteries containing hybrid graphene
Patent Information
- Application Number
- JP2024546028
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-04
- Filing Date
- 2022-09-28
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2042-09-28
AI Technical Summary
【0022】 本発明に係るリチウムイオン電池用負極は、光化学、光熱照射または熱処理工程方式で製造された3次元多孔性ハイブリッドグラフェン複合体を負極活物質として含むことで、安定したグラフェン複合体構造を形成し、高い電気伝導性で充放電速度および効率を顕著に改善させ、リチウムイオンが結合することができる容量を極大化させて性能および安定性を満遍なく備えたリチウムイオン電池を実現することができる。
Smart Images

Figure 2025505161000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an anode for a lithium ion battery, and more particularly to an anode including a graphene-based composite material (hybrid graphene) as an anode active material and a lithium ion battery related thereto. [Background technology]
[0002] There are various types of secondary batteries that can be charged and discharged, such as lead-acid batteries and nickel-metal hybrid batteries. Among them, lithium-ion batteries (LIBs) have a high energy density, high output density, and an operating voltage that can withstand long charging and discharging periods. Due to these characteristics, they are widely used not only as batteries that supply power to portable mobile devices such as smart phones and netbooks, but also as energy supply components for hybrid vehicles.
[0003] In lithium-ion batteries, the positive electrode active material is changing in various ways to improve its performance. However, even if the positive electrode material generates high energy, if the negative electrode material, which stores it, does not support it in a balanced manner, the efficiency will be inferior. In particular, charging time can be reduced only if the negative electrode material is designed to absorb lithium ions well during charging. Graphite has long been used as a negative electrode active material. Graphite has a layered structure in which layers of carbon bonded in a regular pattern are stacked on top of each other. During the charging process, when lithium ions move from the positive electrode to the negative electrode, the lithium ions that reach the negative electrode are stored between the graphite layers.
[0004] Currently, research is being conducted into new materials that can replace the existing graphite anode material in order to improve the performance of lithium-ion batteries. Graphite has low electrical conductivity, which means it takes a long time to charge and discharge, and it does not have a high charging capacity because it does not have enough capacity to bind lithium ions.
[0005] Therefore, there is a need to develop a new anode material that can solve or mitigate the above problems and improve the properties of the anode material compared to the conventional technology, thereby increasing the charging capacity and battery life of the lithium-ion battery and shortening the charging time. Summary of the Invention [Problem to be solved by the invention]
[0006] The technical problem to be solved by the present invention is to solve the problems of conventional lithium ion batteries including graphite as an anode active material layer, in which graphite has a long charge / discharge time due to its low electrical conductivity and a low charging capacity due to its insufficient capacity for lithium ions to bind, and to provide a lithium ion battery anode including hybrid graphene having a graphene composite multilayer structure in which metal or semiconductor particles are fused and bonded to graphene to form a three-dimensional network, and a lithium ion battery including the same. [Means for solving the problem]
[0007] In order to overcome these problems, the present invention proposes a hybrid graphene structure in which metal or semiconductor particles are interconnected with a graphene multilayer to form a network structure, and the metal or semiconductor particles can be maintained in a stable state even when charging and discharging are repeated. Conventional processes for mixing graphene with metal or semiconductor particles are simply mixed with already-produced graphene, and therefore the organic bonding strength between the metal or semiconductor particles and graphene is insufficient.
[0008] In the present invention, since graphene is produced by mixing metal or semiconductor fine particles, the surfaces of the metal or semiconductor fine particles are melted and solidified with the graphene, and the fine particles and the graphene form a three-dimensional nanostructure and are bonded to each other.
[0009] In addition, since the formed graphene composite is composed of multi-layer graphene, it has a structural feature in which metal or semiconductor microparticles are bound to the surface or inside of the multi-layer graphene and the graphene composite layers are filled between the silicon microparticles to interconnect them.
[0010] In this manner, the negative electrode active material pseudo structure made of a graphene composite having a structure in which metal or semiconductor fine particles and multilayer graphene are mixed has the following effects.
[0011] First, the surface of the metal or semiconductor nanoparticles is completely coated with graphene, which effectively suppresses the volume expansion caused by the binding of the metal or semiconductor nanoparticles with lithium ions, thereby resolving the problems of metal or semiconductor particles being broken and separated from the electrode due to excessive volume expansion and contraction.
[0012] Second, the multi-layer graphene layer acts as a scaffold that fixes the position of metal or semiconductor. Theoretically, graphene has a tensile strength 200 times stronger than steel, so it does not easily break even when bent. Therefore, when graphene is combined with metal or semiconductor microparticles to form a multi-layer structure, the position of the metal or semiconductor microparticles is fixed, and it acts as a scaffold that maintains a stable structure even when the metal or semiconductor changes shape due to charging and discharging.
[0013] Third, graphene has high electron mobility and current density, which facilitates electron transfer with lithium ions, thereby increasing the charge and discharge speed by facilitating electron transfer with metal or semiconductor microparticles, and improving the charge and discharge efficiency of the graphene metal or semiconductor composite structure.
[0014] In order to achieve the above technical objectives, the present invention provides a negative electrode for a lithium ion battery, comprising a negative electrode active material made of a hybrid graphene composite, the hybrid graphene composite having a three-dimensional structure in which a plurality of layers of graphene are stacked and bent in any direction, the metal particles are bonded to a surface or inside of the graphene, some fine metal particles are bonded and solidified with each other, and some of the spaces between the metal particles are filled with the graphene composite layer and interconnected with each other.
[0015] The present invention also provides a negative electrode for a lithium ion battery, characterized in that the fine metal particles have surfaces coated with graphene.
[0016] The present invention also provides a negative electrode for a lithium ion battery, wherein the graphene-metal composite is produced by a photochemical, photothermal irradiation, or heat treatment process.
[0017] In addition, the metal or semiconductor particles of the present invention are made of silver (Ag), silicon (Si), silicon carbide (Si2C, SiC or SiC2). X ), silicon oxide (SiO or SiO2 containing X ), silicon composite oxide (Si-Mg x SiO x The present invention provides a negative electrode for a lithium ion battery, which is characterized in that the negative electrode is made of a metal or a semiconductor selected from the group consisting of tantalum oxide (Au), magnesium metasilicate (enstatite, MgSiO3), forsterite (forsterite, Mg2SiO4), gold (Au), platinum (Pt), palladium (Pd), aluminum (Al), zinc (Zn), a silver alloy (Ag alloy), copper (Cu) having a silver (Ag)-coated surface, and silver (Ag) having a copper (Cu)-coated surface.
[0018] In addition, the hybrid graphene composite of the present invention provides a negative electrode for a lithium ion battery, which has a network structure formed by interconnecting the three-dimensional porous graphene structure and the metal particles.
[0019] The present invention also provides an all-solid-state battery including a positive electrode including a positive electrode current collector and a positive electrode active material layer, a solid electrolyte layer, and the negative electrode.
[0020] The present invention also provides an all-solid-state battery, characterized in that the positive electrode active material layer contains one or more positive electrode active materials selected from the group consisting of lithium-nickel-cobalt-manganese composite oxides (NCM), lithium-nickel-cobalt-aluminum composite oxides (NCA), lithium-cobalt composite oxides (LCO), and lithium-nickel composite oxides (LNO).
[0021] The present invention also provides an all-solid-state battery, wherein the solid electrolyte layer includes one or more solid electrolytes selected from the group consisting of Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-GeS2, and Li2S-SiS2-Li3PO4. Effect of the Invention
[0022] The negative electrode for a lithium ion battery according to the present invention includes a three-dimensional porous hybrid graphene composite prepared by a photochemical, photothermal irradiation, or heat treatment process as a negative electrode active material, thereby forming a stable graphene composite structure and remarkably improving charge / discharge speed and efficiency due to high electrical conductivity, and maximizing the capacity in which lithium ions can be bound, thereby realizing a lithium ion battery with well-balanced performance and stability. [Brief description of the drawings]
[0023] [Figure 1a]1 is a scanning electron microscope (SEM) photograph and a conceptual diagram showing silver particles (Ag) before a photothermal irradiation step is carried out. [Figure 1b] 1 is a scanning electron microscope (SEM) photograph showing silver particles (Ag) after a photothermal irradiation step is performed. [Figure 1c] 1 is a scanning electron microscope (SEM) photograph showing a porous graphene structure (3D nanoporous graphene) produced by photochemical, photothermal irradiation, or heat treatment without metal particles. [Figure 1d] 1 is a scanning electron microscope (SEM) photograph showing a hybrid graphene composite for use as a negative electrode active material in an all-solid-state battery produced by photochemical, photothermal irradiation, or heat treatment in an embodiment of the present application. [Figure 1e] FIG. 1 is a conceptual diagram showing a structure in which graphene prepared by the photochemical, photothermal irradiation, or heat treatment reaction (d) in an embodiment of the present application is located and fixed in the vacant space (b) of silver (Ag) microparticles. [Diagram 2] 1 is a graph showing current measurement results depending on the concentration of an electrochemically measured substance (PAP) for a hybrid graphene composite electrode (graphene-Ag electrode) for an all-solid-state battery negative electrode active material according to the present invention, a graphene electrode, and a metal electrode (gold electrode). [Diagram 3] 1 is a graph showing a comparison of current values at the same concentration (10-3 mM) of PAP for a hybrid graphene composite (Hybrid Graphene) for an all-solid-state battery negative electrode active material according to the present invention, graphene (Graphene), and metal (Metal (Au)). [Figure 4] 1 is a real-time graph showing the measurement of various concentrations of an electrochemically measured substance (PAP) using the hybrid graphene electrode for an anode of an all-solid-state battery according to the present invention. [Diagram 5]FIG. 1 is a cross-sectional schematic diagram of an example of an all-solid-state battery including a negative electrode for an all-solid-state battery according to the present invention, the all-solid-state battery including a positive electrode including a positive electrode active material (NMC), a sulfide-based solid electrolyte layer, and a negative electrode current collector (SUS), and a negative electrode including a negative electrode active material layer including a negative electrode active material made of the hybrid graphene composite. [Figure 6] 1A and 1B are photographs showing cross sections of a negative electrode for an all-solid-state battery comprising the hybrid graphene composite of the present invention in a charged state (a) and a discharged state (b). [Figure 7] Photographs of the hybrid graphene anode (left) and a coin cell battery (right) fabricated using the hybrid graphene anode of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] In describing the present invention, if it is determined that a detailed description of related known functions or configurations may make the gist of the present invention unclear, the detailed description will be omitted.
[0025] Since the embodiment according to the concept of the present invention can be modified in various ways and can have various forms, a specific embodiment will be illustrated in the drawings and described in detail in the specification or application. However, this is not intended to limit the embodiment according to the concept of the present invention to the specific disclosed form, and it should be understood that the embodiment includes all modifications, equivalents, and alternatives included in the spirit and technical scope of the present invention.
[0026] The terms used in this specification are merely used to describe certain embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless the context clearly indicates otherwise. In this specification, the terms "include" or "have" are intended to specify the presence of a described feature, number, step, operation, component, part, or combination thereof, and should be understood not to preclude the presence or additional possibility of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.
[0027] The present invention will now be described in detail.
[0028] The present invention relates to an all-solid-state battery negative electrode for lithium-ion batteries, and is characterized in that a hybrid graphene composite, which is a composite material of graphene and metal particles, is used as the negative electrode active material.
[0029] The hybrid graphene composite is an anode material constituting the anode active material layer, and is formed in a lithium ion battery. It absorbs lithium (Li) during charging, and after the charging capacity is exceeded, it covers the metallic lithium layer deposited at the interface between the anode current collector and the anode active material layer, thereby acting as a protective layer for the lithium metal layer. At the same time, it inhibits excessive growth of lithium dendrites, blocks their penetration into the solid electrolyte layer, and induces uniform growth of lithium dendrites, thereby preventing short circuits and capacity reduction in the all-solid-state battery, and as a result, the performance of the all-solid-state battery can be improved.
[0030] At this time, graphene constituting the hybrid graphene composite has high electron mobility, which allows uniform and smooth electron supply, thereby increasing the charge / discharge speed and efficiency of the all-solid-state battery. In addition, graphene has a high Young's modulus, which can efficiently support the expansion of the negative electrode active material caused by the binding of metal particles such as silver (Ag) particles with lithium (Li).
[0031] On the other hand, the graphene constituting the hybrid graphene composite is preferably derived from a three-dimensional porous graphene structure rather than pure graphene without defects.
[0032] The hybrid graphene composite has a three-dimensional structure in which a plurality of layers of graphene are stacked and bent in an arbitrary direction, the metal particles are bonded to the surface or inside of the graphene by photochemistry, photothermal irradiation, or heat treatment, and some fine metal particles are mutually bonded and solidified, A portion of the vacant space between the metal particles is filled with the graphene composite layers, resulting in an interconnected structure.
[0033] The fine metal particles may have a structure in which the surfaces are coated with graphene.
[0034] Pure graphene without defects has excellent physical properties such as excellent electrical conductivity and high specific surface area, but the advantage of high specific surface area is greatly reduced due to irreversible self-aggregation.
[0035] Meanwhile, a 3D porous graphene structure in which pores are organically connected in a 3D manner between layers and / or multiple graphene sheets exhibits relatively superior properties in electrochemical applications such as energy conversion and storage devices, since it has a relatively larger specific surface area due to a reduced self-aggregation phenomenon and can diffuse electrons and ions more quickly. In addition, the 3D porous graphene structure has the advantage that it is also possible to control the pore characteristics (position and size of pores, etc.) by controlling process variables during the manufacturing process.
[0036] Furthermore, the 3D porous graphene structure can adjust its electrical properties by changing the electronic structure of graphene through chemical doping, which adsorbs different materials such as metal particles, like the graphene-metal particle composite according to the present invention.
[0037] Meanwhile, the method for manufacturing the 3D porous graphene structure is not particularly limited, but mainly uses a method using a hard template or a soft template. Methods using the hard template include a method using a spherical polymer, a method using metal oxide particles, and a method using a porous substrate such as nickel foam. The soft template method can synthesize a material with a controlled pore size using a Micellar template made by the self-assembly of surfactant molecules, and has the advantage of being relatively easy to remove the template compared to the hard template method.
[0038] In addition, after forming a polymer coating layer, a stabilization reaction may be induced so that carbon atoms in the polymer have a hexagonal ring arrangement, and the polymer may be carbonized at high temperature to manufacture a 3D porous graphene structure. Specific examples of the polymer include poly(methyl methacrylate) (PMMA), polystyrene (PS), polyimide (PI), polyetherimide (PEI), Kapton film, etc., but the polymer is not necessarily limited thereto. As long as the polymer can be carbonized at high temperature to serve as a carbon source to form graphene, there are no particular restrictions on its structure, molecular weight, glass transition temperature, etc.
[0039] The metal particles that are combined with the graphene to form the hybrid graphene composite are silver (Ag), silicon (Si), silicon carbide (SiC, SiC, or SiC2), and the like. X ), silicon oxide (SiO or SiO2 containing X ), silicon composite oxide (Si-Mg x SiO x), magnesium metasilicate (enstatite, MgSiO3), forsterite (forsterite, Mg2SiO4), gold (Au), platinum (Pt), palladium (Pd), aluminum (Al), zinc (Zn), silver alloy (Ag alloy), copper (Cu) surface-coated with silver (Ag), and silver (Ag) surface-coated with copper (Cu). Furthermore, the fine particles may be metal or semiconductor particles including a core particle made of one of the metals or semiconductors and a coating layer made of a material different from the core particle (e.g., copper particles coated with silver, silver particles coated with copper, silicon particles coated with an oxide, silicon particles coated with a composite oxide, etc.), but are not necessarily limited to the metal particles mentioned above.
[0040] Taking silver (Ag) particles as an example of the metal particles, silver (Ag) particles dissolve in lithium (Li) and reduce the energy required for lithium to crystallize, which causes lithium to generate pores and grow more uniformly instead of unevenly, ultimately contributing to improved performance of lithium-ion batteries.
[0041] As a method for preparing the hybrid graphene composite by combining graphene and metal particles, a method for uniformly mixing and combining a three-dimensional porous graphene structure and metal particles through a stirring process such as ball milling may be used. More preferably, a mixture of a uniform mixture of a three-dimensional porous graphene structure and metal particles is irradiated with light to sinter the mixture, thereby preparing a hybrid graphene composite having a three-dimensional network structure in which interconnections between metal particles, between graphene sheets, and between metal particles and graphene sheets are organically formed.
[0042] The present invention can also be applied to a lithium ion battery, which is an all-solid-state battery including a solid electrolyte layer. An all-solid-state battery including a negative electrode active material made of the hybrid graphene composite may include a positive electrode including a positive electrode current collector and a positive electrode active material layer, a solid electrolyte layer, and a negative electrode current collector, and a negative electrode including a negative electrode active material layer including a negative electrode active material made of the hybrid graphene composite.
[0043] In this case, the positive electrode active material layer may include one or more positive electrode active materials selected from the group consisting of lithium-nickel-cobalt-manganese composite oxides (NCM), lithium-nickel-cobalt-aluminum composite oxides (NCA), lithium-cobalt composite oxides (LCO), and lithium-nickel composite oxides (LNO), but the constituent materials are not necessarily limited to the positive electrode active materials.
[0044] The type of solid electrolyte constituting the solid electrolyte layer is not particularly limited, but may include a sulfide-based solid electrolyte, and may be, for example, one or more selected from the group consisting of Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-GeS2, and Li2S-SiS2-Li3PO4.
[0045] Hereinafter, the present invention will be described in more detail with reference to the embodiments.
[0046] The embodiments according to the present specification may be modified into various other forms, and the scope of the present specification is not to be construed as being limited to the embodiments described below.
[0047] The embodiments of the present specification are provided in order to more completely explain the present specification to those having average knowledge in the art.
[0048] FIG. 1a is a scanning electron microscope (SEM) photograph showing silver particles (Ag) before a photothermal irradiation step is performed to produce a hybrid graphene composite, which is a negative electrode active material contained in a negative electrode for a solid-state battery according to the present invention.
[0049] Referring to FIG. 1a, the silver (Ag) particles before photothermal irradiation have a spherical particle diameter of about 5 μm.
[0050] FIG. 1b is a scanning electron microscope (SEM) photograph showing silver particles (Ag) after the photothermal irradiation process.
[0051] Referring to FIG. 1b, it was confirmed that the surface of the silver (Ag) particles was melted and bonded to adjacent particles using photothermal irradiation, and some particles were not connected, forming empty spaces.
[0052] FIG. 1c is a scanning electron microscope (SEM) photograph showing a porous graphene structure (three-dimensional nanoporous graphene) before a photothermal irradiation process is performed to produce a hybrid graphene composite, which is a negative electrode active material contained in a lithium ion battery negative electrode according to the present invention.
[0053] Referring to FIG. 1c, it can be seen that the multi-layer graphene has a three-dimensional overlapping or bent structure.
[0054] FIG. 1d is a scanning electron microscope (SEM) image showing a hybrid graphene composite for use as a negative electrode active material for an all-solid-state battery according to the present invention, which is prepared by subjecting a mixture of a three-dimensional porous graphene structure and silver particles (Ag) to a photothermal irradiation process in an embodiment of the present application.
[0055] Referring to FIG. 1d, in the embodiment of the present application, fine metal particles are simultaneously bound to the surface and inside of the graphene composite layer by photochemical, photothermal irradiation, or heat treatment, and at the same time, the fine metal particles are shown to have a fixed structure in which they can be mutually bonded and solidified.
[0056] FIG. 1e is a conceptual diagram showing a structure in which graphene prepared by photochemical, photothermal irradiation, or heat treatment according to d in the embodiment of the present application is located and fixed in the vacant space of silver (Ag) microparticles.
[0057] 1e is a conceptual diagram showing a structure in which graphene produced by photochemistry, photothermal irradiation, or heat treatment is located and fixed in the vacant spaces of silver (Ag) microparticles. The silver (Ag) microparticles can be attached to the inside and outside of the graphene composite layer, and although not shown in the conceptual diagram, some micrometal particles can be mutually bonded and solidified due to the irregular positions of the silver (Ag) microparticles.
[0058] In addition, the silver (Ag) fine metal particles can have a graphene coating on the surface by photochemical, photothermal irradiation, or heat treatment. FIG 1e shows a graphene coating structure on the particle surface.
[0059] Conventional graphene requires complicated processes, including high-temperature processes, but photochemical, photothermal irradiation, or heat treatment synthesized graphene can be synthesized relatively easily in a one-step process.
[0060] FIG. 2 is a graph showing current measurement results depending on the concentration of an electrochemical measurement substance (p-aminophenol, PAP) for a hybrid graphene composite for use as a negative electrode active material in an all-solid-state battery according to the present invention (graphene-Ag electrode), a graphene electrode, and a metal electrode (gold electrode).
[0061] For each electrode, the current signal increases in size with increasing PAP concentration.
[0062] In addition, for the same concentration of PAP, the signal from the graphene electrode, which has advantages in terms of surface area and electron inflow and outflow compared to a metal electrode, was larger, and the signal from the hybrid-graphene composite electrode, which has a smaller resistance compared to the graphene electrode, was measured to be larger.
[0063] FIG. 3 shows the results of the hybrid graphene composite for an all-solid-state battery negative electrode active material according to the present invention, graphene, and metal (Metal (Au)) at the same concentration (10 -3 1 is a graph showing a comparison of current values at PAP of 1 mM.
[0064] 3 is a graph showing the difference in current signal measured for the hybrid graphene electrode (graphene metal composite), metal electrode, and graphene electrode for the negative active material of an all-solid-state battery at the same concentration of PAP. It can be seen that the signal size measured for the graphene metal composite electrode at the same concentration is much larger than that of the comparison electrode. Therefore, it can be seen that the current signal of the graphene metal composite electrode of the present invention generates a larger signal than the comparison electrode, and the SNR (Signal to Noise Ratio) is larger than that of the comparison electrode.
[0065] FIG. 4 is a real-time graph showing the measurement of various concentrations of an electrochemically measured substance (PAP) using the hybrid graphene electrode for an anode of an all-solid-state battery according to the present invention.
[0066] FIG. 5 is a cross-sectional schematic diagram of an example of an all-solid-state battery including the all-solid-state battery negative electrode according to the present invention, the all-solid-state battery including a positive electrode including a positive electrode active material (NMC), a sulfide-based solid electrolyte layer, and a negative electrode current collector (SUS), and a negative electrode including a negative electrode active material layer including a negative electrode active material made of the hybrid graphene composite.
[0067] FIG. 6 is a set of photographs showing cross sections of a negative electrode for an all-solid-state battery including the hybrid graphene composite of the present invention in a charged state (a) and a discharged state (b).
[0068] The problem with existing anodes is that lithium is uneven, pores are generated, and deposition occurs in the form of dendrites, but fine silver metal particles dissolve in lithium, lowering the energy at which lithium crystallizes, allowing lithium to grow evenly. Graphene also prevents lithium metal from growing and coming into direct contact with the solid electrolyte, preventing the solid electrolyte from being decomposed and improving durability.
[0069] It acts as a three-dimensional host where lithium metal is deposited and as a protective layer to protect the solid electrolyte, improving durability.
[0070] FIG. 7 shows the hybrid graphene anode (left) prepared according to the present invention and a coin cell battery (right) prepared using the same.
[0071] The present invention described above is not limited to the above-described embodiments and the accompanying drawings, and it will be apparent to those having ordinary skill in the art to which the present invention pertains that various replacements, modifications and alterations are possible within the scope of the technical idea of the present invention.
Claims
1. The negative electrode active material includes a graphene composite having a structure in which a plurality of micro particles and multi-layer graphene are mixed, The fine particles are metal or semiconductor particles, and are attached to the surface or inside of the multi-layer graphene, and some of the fine particles are mutually bonded and solidified; The multi-layer graphene has a three-dimensional structure in which a plurality of layers of graphene are stacked and bent in an arbitrary direction, The fine particles are attached to the surface or inside of the graphene, The negative electrode for a lithium ion battery comprising hybrid graphene, wherein a portion of the vacant space between the fine particles is filled with the graphene composite and has an interconnected structure.
2. The negative electrode for a lithium ion battery comprising the hybrid graphene according to claim 1 , characterized in that the surface of the fine particles is coated with graphene.
3. 2. The negative electrode for a lithium ion battery comprising the hybrid graphene according to claim 1, wherein the surfaces of the fine particles are melted and solidified with the graphene, and the fine particles and the graphene form a three-dimensional nanostructure and are bonded to each other.
4. The negative electrode for a lithium ion battery comprising the hybrid graphene according to claim 1 , wherein the graphene composite is produced by a photochemical, photothermal irradiation, or heat treatment process.
5. The fine particles are made of silver (Ag), silicon (Si), silicon carbide (Si 2 C, SiC or SiC 2 Including SiC X ), silicon oxide (SiO or SiO 2 SiO X ), silicon composite oxide (Si-Mg x SiO x ), magnesium metasilicate (enstatite, MgSiO 3 ), forsterite (Mg 2 SiO 4 2. The negative electrode for a lithium ion battery comprising the hybrid graphene according to claim 1, characterized in that the negative electrode is made of a metal or a semiconductor selected from the group consisting of: Zn, gold (Au), platinum (Pt), palladium (Pd), aluminum (Al), zinc (Zn), a silver alloy (Ag alloy), copper (Cu) whose surface is coated with silver (Ag), and silver (Ag) whose surface is coated with copper (Cu).
6. The graphene composite is a three-dimensional porous graphene structure, 2. The negative electrode for a lithium ion battery comprising the hybrid graphene of claim 1, wherein the fine particles are interconnected to form a network structure.
7. a positive electrode including a positive electrode current collector and a positive electrode active material layer; A solid electrolyte layer; A lithium ion battery comprising the negative electrode according to any one of claims 1 to 6.
8. 8. The lithium ion battery according to claim 7, wherein the positive electrode active material layer contains one or more positive electrode active materials selected from the group consisting of lithium-nickel-cobalt-manganese composite oxides (NCM), lithium-nickel-cobalt-aluminum composite oxides (NCA), lithium-cobalt composite oxides (LCO), and lithium-nickel composite oxides (LNO).
9. 8. The lithium ion battery according to claim 7, wherein the solid electrolyte layer comprises one or more solid electrolytes selected from the group consisting of Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-GeS2, and Li2S-SiS2-Li3PO4.
Citation Information
Patent Citations
Graphene material with randomly distributed two-dimensional structural defects
JP2014518835A
Flexible carbon pocket composite structure, method for manufacturing the same, electrode including the same, and energy storage device including said electrode
JP2019511982A
MANUFACTURING METHOD OF GRAPHENE-Si COMPOSITE
JP2020033244A
Multi-layered graphene material having a plurality of yolk / shell structures
KR1020170094459A
Server for Recommending Stock Trading based on Valuation using Big data and Program for Recommending Artificial Intelligence Stock Trading based on Valuation
KR1020220097189A